The family support role in hospital rapid response teams: a scoping review protocol. Issue 6 (3rd June 2021) - Howlett, Owen; Gleeson, Rebecca; Arntzen, Heidi; Truscott, Myf; Adams, Robin; Howie, Caitlin; French, Rebecca; Rowe, Elizabeth; Maggs, Julie-Anne; Kennedy, Sheridan; Jackson, Lana
ABSTRACT: Objective: The objective of this review is to identify and understand how a family support role has been delivered in rapid response teams in hospital settings. Introduction: A family support role in a hospital rapid response team is a designated position that is responsible for supporting the family members of people being medically attended to during a hospital rapid response. Support may include the provision of guidance to the family regarding a hospital procedure, support whilst witnessing the rapid response, or assisting the family to process their emotional response. This review will assist in identifying the ways in which the family support role is delivered in rapid response teams within a hospital environment. Inclusion criteria: Family support must be delivered by a person who has a designated family support role within a rapid response team in a hospital setting. Studies will not be limited to geographical location, gender, or culture. Studies are not limited to year of publication or methodological design. Methods: Databases will include MEDLINE (Ovid), Embase (Ovid), CINAHL, and Cochrane. Gray literature will be searched with predetermined search criteria. Two independent authors will be used to screen articles and perform data extraction on a predetermined data extraction form. A narrative Summary of Findings is planned, alongside a presentation of the data in diagrammatic or tabular form.